A study on analysis of fetal heart rate abnormalities comparing epidural analgesia ropivacaine 0.2% plus fentanyl 2 μg/ml with bupivacaine 0.1% plus fentanyl 2 μg/ml during labour - Angeline Peter, Mary (2014)

(untitled)
Title: A study on analysis of foetal heart rate abnormalities comparing epidural analgesia ropivacaine 0.2% with fentanyl 2ug/ml to bupivacaine 0.1% with fentanyl 2ug/ml during labour. Background and Objectives: Epidural analgesia effectively relieves labour pain and is widely chosen by parturients. Foetal well being is also important during labour as various neuraxial analgesia in labour is known to influence FHR tracings. Various studies focused on equipotent doses of local anesthetics and compared different techniques of labour analgesia in assessing foetal heart rate changes and its outcome on mode of delivery, effects on maternal haemodynamics and the neonatal outcome based on APGAR score. Therefore, this study was intended to analyze foetal heart rate changes using two different concentrations of epidural analgesia with opioids and its effect on the mode of delivery, maternal haemodynamics and neonatal outcome. Methodology: A total of 126 patients were recruited in this prospective randomized cross sectional study. Maternal haemodynamics and foetal heart rate monitoring is documented 15 minutes before epidural administration and 15 minutes after epidural administration and subsequently every 30 minutes till four hours. CTG interpretation is documented. The observed outcome in this study were foetal heart rate abnormalities post epidural, maternalhaemodynamics before and after epidural analgesia in labour, mode of delivery and the neonatal APGAR score. Result: Based on the mode of delivery between both the groups of epidural analgesia ropivacaine and bupivacaine, there were 48 (71.6%) in the ropivacaine group and 49 (83.1%) in the bupivacaine group who delivered spontaneously. 4 (6%) only delivered via instrumental in the ropivacaine group. Via caesarean section 15 (22.4%) in the ropivacaine group and 10 (16.9%) in the bupivacaine group. There were no significant changes in the mode of delivery between both the groups. 115 parturients had normal FHR, 96(83.5%) delivered spontaneously, 2 (1.7%) had instrumental delivery, 17 (14.8%) delivered via caesarean section. Whereas 11 patients had abnormal FHR, 1 (9.1%) delivered spontaneously, 2 (18.2%) via instrumental delivery and 8 (72.7%) via caesarean delivery. A higher percentage in caesarean delivery with abnormal CTG with a significant p value <0.001. Parturients for caesarean section were 27, 18 had normal CTG out of which 4 (22.2%) for secondary arrest, 2 (11.1%) for acute foetal distress, 12 (66.7%) for poor progress. 9 parturients had abnormal CTG, out of which 1 (11.1%) for secondary arrest, 8 (88.9%) for acute foetal distress with a significant p value=<0.001.There were no significant difference seen in maternal outcome and neonatal outcome. Conclusion: This study revealed that with epidural analgesia in labour using ropivacaine 0.2% and bupivacaine 0.1% with fentanyl 2ug/ml, there were no foetal heart rate changes. There were increased risk for caesarean delivery with abnormal CTG in the ropivacaine group due to acute foetal distress. There were no changes in the maternal and neonatal outcome.